Bringing Redox Reactivity to a Redox Inactive Metal Center – E–I (E = C, Si) Bond Cleavage with a Thorium Bis(α‐diimine) Complex. Issue 22 (23rd May 2013) - Mrutu, Agnes; Barnes, Charles L.; Bart, Suzanne C.; Walensky, Justin R.
Abstract: As the reactivity of transition‐metal complexes with redox‐active ligands has gained significant attention in recent years, we have begun expanding to the actinides. Here, we report the synthesis, characterization, and reactivity of ( Mes DAB Me )2 Th(THF) {1, Mes DAB Me = [MesNC(Me)=C(Me)NMes] 2–, Mes = 2, 4, 6‐trimethylphenyl, THF = tetrahydrofuran}, which cleaves the C–I bond in CH3 I with subsequent Th–I and C–C bond formation to produce ( Mes DAB Me )( Mes DAB   Me   2 )ThI {2, Mes DAB   Me   2 = [MesN=C(Me)C(Me)2 NMes] – }. When2 is crystallized in acetonitrile, the solvated adduct ( Mes DAB Me )( Mes DAB   Me   2 )ThI(NCCH3 ) (2 ‐MeCN) is isolated. The reaction of 2 equiv. of1 with Me3 SiI produces ( Mes DAB Me )2 ThI (3 ) and Me3 SiSiMe3 . In3, one Mes DAB Me ligand is now monoanionic and provides an electron to cleave the Si–I bond. This represents a rare example of the reactivity of thorium with a redox‐active ligand. Abstract : The reactivity of a redox‐active thorium(IV) complex with CH3 I and Me3 SiI is shown to be divergent. This is a rare example of the use of redox‐active ligands with the actinides.